Acetoxyroyleanone exhibits selective anti-cancer effects and induces apoptosis in human colon carcinoma cells through the mediation of NF-kappaB and caspase-3 signalling pathways (Bangladesh Journal of Pharmacology, 2016)
The objective of the current study was to evaluate the antiproliferative and apoptotic activities of acetoxyroyleanone against various cancer cells along with studying its effect on chromatin condensation, NF-?B and caspase-3 expressions and cell migration. 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay was used to evaluate cell viability while as fluorescence microscopy revealed the effects of acetoxyroyleanone  on cellular morphology of Colo-205 cells. Western blotting revealed effects on NF-?B and caspase-3 expressions. The results revealed that acetoxyroyleanone  induced potent and dose-dependent antiproliferative effects against a range of cancer cell lines with Colo-205 being the most susceptible cell line. However, it required six to eight times higher concentration of acetoxyroyleanone to induce 50% cell death in normal epithelial (fR-2) cell line. Further, following acetoxyroyleanone treatment to Colo-205, it was observed that acetoxyroyleanone induced substantial down-regulation of NF-?B and up-regulation of caspase-3 expressions. In addition, acetoxyroyleanone impairs cell migration, chromatin condensation, cell shrinkage and membrane blebbing.